The Role of Biologic Agents in the Non-operative Management of Elbow Ulnar Collateral Ligament Injuries - Apostolakos, John M. (Curr Rev Musculoskelet Med, 2020)
PURPOSE OF REVIEW: Injuries to the elbow ulnar collateral ligament (UCL) are especially common in the overhead throwing athlete. Despite preventative measures, these injuries are occurring at increasing rates in athletes of all levels. UCL reconstruction techniques generally require a prolonged recovery period and introduce the potential for intraoperative complications prompting investigations into more conservative treatment measures based on specific patient and injury characteristics. The purpose of this review is to describe the current literature regarding the use of biologic augmentation in the management of UCL injuries. Specifically, this review will focus on the basic science background and clinical investigations pertaining to biologic augmentation utilizing platelet-rich plasma (PRP) and autologous stem cells. RECENT FINDINGS: Despite some evidence supporting the use of PRP therapy in patients with partial UCL tears, there is no current consensus regarding its true efficacy. Similarly, due to a lack of clinical investigations, no consensus exists regarding the utilization of autologous stem cell treatments in the management of UCL injuries. SUMMARY: Management of UCL injuries ranges from non-operative treatment with focused physical therapy protocols to operative reconstruction. The use of biologic augmentation in these injuries continues to be investigated in the orthopedic community. Currently, no consensus exists regarding the efficacy of either PRP or autologous stem cells and further research is needed to further define the appropriate role of these treatments in the management of UCL injuries.